2015
DOI: 10.1007/s00299-015-1874-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic and epigenetic changes in virus-free garlic (Allium sativum L.) plants obtained by meristem culture followed by in vitro propagation

Abstract: This is the first report assessing epigenetic variation in garlic. High genetic and epigenetic polymorphism during in vitro culture was detected.Sequencing of MSAP fragments revealed homology with ESTs. Garlic (Allium sativum) is a worldwide crop of economic importance susceptible to viral infections that can cause significant yield losses. Meristem tissue culture is the most employed method to sanitize elite cultivars.Often the virus-free garlic plants obtained are multiplied in vitro (micro propagation). How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…Harding [ 77 ] and Peredo et al [ 80 , 81 ] attributed the DNA methylation changes detected in slow growth to the in vitro culture procedures. Studies of the effect of tissue culture on the DNA methylation stability have detected significant changes, as for example the work of Gimenez et al [ 89 ], on in vitro propagated garlic, a species usually conserved in germplasm banks through slow growth storage. These authors, using MSAP, detected changes, mainly demethylations, in plants under prolonged in vitro culture.…”
Section: In Vitro Plant Conservationmentioning
confidence: 99%
“…Harding [ 77 ] and Peredo et al [ 80 , 81 ] attributed the DNA methylation changes detected in slow growth to the in vitro culture procedures. Studies of the effect of tissue culture on the DNA methylation stability have detected significant changes, as for example the work of Gimenez et al [ 89 ], on in vitro propagated garlic, a species usually conserved in germplasm banks through slow growth storage. These authors, using MSAP, detected changes, mainly demethylations, in plants under prolonged in vitro culture.…”
Section: In Vitro Plant Conservationmentioning
confidence: 99%
“…For instance, Rhee et al [7] demonstrated the silencing of epialleles by epigenetic modifications and showed that the pericarp color1 (p1) epialleles were capable of functioning in the presence of the correct trans-acting factors in maize. Furthermore, there are many reports on epigenetic changes caused by plant regeneration in rice [9], garlic [10], triticale [11], pineapple [12], torenia, and rye [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to genotype, the culture medium also induces variations in gene regulation, chromatin structure and the epigenome [19][20][21]. Epigenetic changes are reported during the regeneration of rye [22], triticale [23], garlic and torenia [24,25]. Furthermore, the use of demethylating agents, such as 5-azacytidine (5-azaC), has led to differential transcriptional activities in regenerants, implying that changes in DNA methylation induced through in vitro culture may regulate gene expression, resulting in phenotypic variations [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%